Higher Childhood Adversity Reduces Environmental Satisfaction Among Older Adults. (17th December 2021) - Danielson, Ramona; Ray-Degges, Susan
Abstract: Background: Childhood adversity (CA) is associated with increased physiological and psychological challenges in adulthood. Normal aging comes with changes that may put adults with a history of CA at increased risk of a poor quality aging experience. Because suitable person-environment fit is an important component of well-being, the present study explored two hypotheses: 1) Higher CA is associated with lower perceived neighborhood quality, and 2) Higher CA is associated with higher perceived inequality in home. Methods: Using MIDUS 2011-2014 Refresher Survey (for this study, N=1, 017 adults ages 55-76), Spearman's rho correlation coefficients were run to explore the associations between a previously validated CA score and two environmental satisfaction indices. Perceived inequality in home comprised ratings on six items and perceived neighborhood quality comprised ratings on four items. Results: Hypothesis 1: There was a significant positive association between the perceived inequality in home and cumulative CA, rs(998) = .200, p < .001. Hypothesis 2: There was a significant negative association between the perceived quality of neighborhood index and cumulative CA, rs(998) = -.182, p < .001. The strength of the associations were weak. Conclusions: Higher cumulative experiences of CA were associated with increased feelings of home environment inequality, and decreased feelings of neighborhood quality. Significant differences were evident after decades had elapsed, demonstrating the long-lasting reach of CA. Further research exploring policy and practice approaches to mitigating the effects of CA is needed to allow aging adults to achieve better person-environment fit and equitable access to successful aging.